The Concept of the Ideal Couple: Buya Hamka's Perspective in Islamic Marriage Law - Chaidir Ali Ahmad; Muhsan Syarafuddin; Kirama Nasim Manbi Ushama; Jamaluddin Jamal Muhsen (Yayasan Cendekia Gagayunan Indonesia, 2025)
The choice of a life partner is a fundamental aspect in Islamic marriage law because it has a direct effect on the formation of a harmonious family. This study aims to analyze Buya Hamka's perspective on the criteria for ideal couples in Islamic marriage and its relevance to contemporary legal and social contexts. This research uses a qualitative approach through literature studies, with the main source in the form of Buya Hamka's works, including Tafsir al-Azhar, Great Pribadi, Living Institutions, and Modern Sufism. The results of the study show that Buya Hamka places faith and morals as the main foundation in choosing a partner, outperforming physical, economic, and social status considerations. In addition, Hamka emphasized the concept of kafā'ah which is not solely material, but includes the harmony of religious understanding, education, character, and vision of life. This view is in line with the purpose of marriage in Indonesia's positive law which emphasizes the formation of a happy, prosperous, and sustainable family. This research contributes by enriching the treasure of Islamic family law thought through the formulation of ideal couple criteria based on the integration of religious, social, and psychological values that are relevant to strengthening the resilience of Muslim families in the modern era.